2011
DOI: 10.3382/ps.2010-01179
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage on the position of the germinal disc in the fertilized unincubated chicken egg

Abstract: The breeding of male layer chickens is currently considered to be highly uneconomical. In Germany alone, 40 to 50 million newly hatched male chickens were killed annually immediately after hatching. Therefore, it is necessary to find a method for sexing chickens early in the embryonic development, preferably before incubation. The genotypic sex of an egg can be determined using information found in the germinal disc, so knowledge of the exact position of the germinal disc is essential for further sexing, or fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…Hence, similar to MRI ( Hutchison et al, 1992 ; Klein et al, 2002 ; Burkhardt et al, 2011 ), CT imaging can help to localise the position of the blastoderm, as confirmed in this study and others ( Bartels et al, 2008 ), which might be particularly interesting to develop tools that require information from the embryo. For example, identifying the exact position of the blastoderm on the yolk may help in developing sexing methods, as suggested previously ( Burkhardt et al, 2011 ) and to differentiate an early-dead embryo from an unfertilised germinal disc ( Bakst et al, 2016a ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Hence, similar to MRI ( Hutchison et al, 1992 ; Klein et al, 2002 ; Burkhardt et al, 2011 ), CT imaging can help to localise the position of the blastoderm, as confirmed in this study and others ( Bartels et al, 2008 ), which might be particularly interesting to develop tools that require information from the embryo. For example, identifying the exact position of the blastoderm on the yolk may help in developing sexing methods, as suggested previously ( Burkhardt et al, 2011 ) and to differentiate an early-dead embryo from an unfertilised germinal disc ( Bakst et al, 2016a ).…”
Section: Discussionsupporting
confidence: 72%
“…Long storage induces an alteration of many egg quality features including a decrease in yolk and albumen quality parameters and water loss, but also impairs the quality of the blastoderm (increased diameter, small shift of its position on the yolk likely due to the progressive disintegration of the chalazae, decreased number of viable cells, increased necrosis and apoptosis, etc.) ( Burkhardt et al, 2011 ; Bakst et al, 2012 ; Abioja et al, 2021 ) ( Figure 1 ). These combined alterations result in an increase of early and late embryo mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these obvious advantages, the application of MRI for monitoring tumor growth in ovo has not been investigated. So far the application of in ovo MRI has been limited to monitoring the growth of the main organs of embryos, such as brain , heart , liver , eyes , limbs , and the germinal disc .…”
Section: Introductionmentioning
confidence: 99%
“…The findings of highest albumen rate and lowest yolk rate in the chukar eggs stored horizontally might also indicate durability of those stored in long-term storage. According to the findings in the study by Burkhardt et al [ 30 ], eggs placed with horizontal position in the last days of the storage were essential for proper location of germinal disc.…”
Section: Discussionmentioning
confidence: 99%